Selection of extractant in rare earth solvent extraction system: A review - Nurul Ain, Ismail; Mohd Aizudin, Abd Aziz; Mohd Yusri, Mohd Yunus; Anwaruddin, Hisyam (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The process of separation, extraction, and purification in obtaining rare earth metals from the minerals is a tedious work due to the similarity of the rare earth metals in chemical and physical properties. Besides designing the rare earth extraction sequence and removing the impurities, the selection step for the type of extractant is also a crucial phase. There are numerous possible combinations of extractant – metal in rare earth separation, ranging from single extractant system to multiple extractant systems. This paper aimed to guide and suggest the best extractant, subject to the leaching condition and the targeted end product. Each type of extractant is revised separately in providing the mechanism and interaction of the rare earth metals. This paper also evaluate the past and current trends of these extractants besides identifying their strong point and the drawbacks.